Experimental Investigation on the Emission Characteristics of a Dual – Fuel Micro Gas Turbine by Injecting Ethanol into Compressor Inlet Air - J. Al-Saraf, Abdul Satar; Al-Jumaily, Suhad A. R. (Al-Khwarizmi Engineering Journal, 2017)
Pollutants generation is strongly dependant on the firing temperature and reaction rates of the gaseous reactants in the gas turbine combustion chamber. An experimental study is conducted on a two-shaft T200D micro-gas turbine engine in order to evaluate the impact of injecting ethanol directly into the compressor inlet air on the exhaust emissions. The study is carried out in constant speed and constant load engine tests. Generally, the results showed that when ethanol was added in a concentration of 20% by volume of fuel flow; NOx emission was reduced by the half, while CO and UHC emissions were almost doubled with respect to their levels when burning conventional LPG fuel alone.